Protection against heirs who make transactions of sale of inheritance land without the consent of other heirs according to law (Study Putusan 70/PDT.6/2006/PN. MDN) - Widodo Ramadhana; O.K. Isnainu; Rodiatun Adawiyah; Muhammad Arif Prasetyo; Atika Sunarto; Santo Satria Simanjuntak (Journal Equity of Law and Governance, 2024)
Soil is essential for life, and Indonesian law regulates land ownership, including the transfer and inheritance of land rights. Disputes often arise when land is sold without the consent of all heirs, leading to legal challenges. This study addresses two main research problems: the procedures for selling inherited land and the responsibilities of defendants in case No. 70/Pdt.6/2006/PN. Mdn. It aims to examine these procedures and determine defendant responsibilities. Using a juridical-normative approach, the study relies on legal principles and secondary data from legal documents, laws, and court decisions. Data collection methods include literature review and field research. Findings indicate that selling inherited land requires the consent of all heirs and compliance with legal requirements. Disputes arise when these requirements are not met, leading to legal actions that can invalidate transactions and restore original positions. Adhering to legal protocols is crucial to prevent disputes and protect heir rights.